2015
DOI: 10.1016/j.cub.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A Non-canonical Pathway from Cochlea to Brain Signals Tissue-Damaging Noise

Abstract: Summary Intense noise damages the cochlear organ of Corti, particularly the outer hair cells (OHCs)[1], however this epithelium is not innervated by nociceptors of somatosensory ganglia, which detect damage elsewhere in the body. The only sensory neurons innervating the organ of Corti originate from the spiral ganglion, roughly 95% of which innervate exclusively inner hair cells (IHCs)[2-4]. Upon sound stimulation, IHCs release glutamate to activate AMPA-type receptors on these myelinated type-I neurons, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 39 publications
7
111
2
1
Order By: Relevance
“…Even though three isoforms of glutamate transporters exist, Vglut3 was targeted because of its role in hearing and pain (Akil et al, 2012; Flores et al, 2015; Ruel et al, 2008; Seal et al, 2009). Here, immunofluorescence was performed to determine whether or not Vglut3 positive neurons would also be Gabrg3 positive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though three isoforms of glutamate transporters exist, Vglut3 was targeted because of its role in hearing and pain (Akil et al, 2012; Flores et al, 2015; Ruel et al, 2008; Seal et al, 2009). Here, immunofluorescence was performed to determine whether or not Vglut3 positive neurons would also be Gabrg3 positive.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the loss of auditory input, noise-induced hearing loss leads to a significant increase in spontaneous activity in the CN. These electrophysiological and neuroanatomical changes have been linked to tinnitus as well as hyperacusis and ear pain (Bauer et al, 2007a; Dong et al, 2009; Flores et al, 2015; Hickox and Liberman, 2014; Kaltenbach et al, 2000). The biological mechanisms that give rise to spontaneous hyperactivity and these perceptual disturbances remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Whether components of the small cell cap or granule cell layers project to central pain pathways remains to be determined. However, recent work has shown that damaging sound increased activity-dependent c-Fos expression in the granule cell region of the cochlear nucleus (39). It also has been suggested that activation of type II afferents drives medial olivocochlear efferents to suppress cochlear sensitivity (40), although that hypothesis is difficult to reconcile with the fact that medial olivocochlear efferents have acoustic tuning and sensitivity similar to those of type I afferents (41).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this extended dendritic arbor, type II afferents are only weakly activated by hair cell glutamate release (Weisz et al 2009;Weisz et al 2012) and are insensitive to sound Robertson 1984;Robertson et al 1999), although they project centrally in parallel with neighboring type I afferents (Berglund and Brown 1994;Brown et al 1988;Brown and Ledwith 1990;Morgan et al 1994). Emerging evidence suggests that type II afferents instead respond to tissue damage (Flores et al 2015;Liu et al 2015) perhaps to serve as cochlear nociceptors. Further insight into type II function will require knowledge of their central connectivity, as well as animal models in which type II function can be altered selectively.…”
Section: Introductionmentioning
confidence: 99%